Nursing care management in the Family Health Strategy: systematic review (Research, Society and Development, 2020)
This study presents the results of a systematic review of the literature on the nursing care management process in the Family Health Strategy. Fifteen articles were analyzed based on the selection in the Virtual Health Library (VHL) databases, in a time frame from 2013 to 2018. The PICO strategy consisting of P (Target Population) I (Area of Interest), C (Context) O (Outcome) as well as the level of evidence. The literature analysis highlights the importance of the nurse inserted in the work process in the Family Health Strategy. The results show that care and management are inextricably linked to the work organization process, one cannot work without the other.